2012
DOI: 10.1097/phm.0b013e31823cb006
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-Guided Intra-Articular Knee Injection in an Obese Patient

Abstract: A 35-yr-old woman was referred to our outpatient clinic for a right intra-articular knee aspiration and injection. She had a medical history notable for lymphedema and morbid obesity (Fig. 1). Her body mass index was recently calculated at greater than 60 kg/m(2). She had a history of four previous nonguided knee joint injections performed elsewhere that provided no significant improvement in pain. On physical examination, it was difficult to localize common knee joint bony landmarks, including the medial and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 2 publications
0
9
0
Order By: Relevance
“…Fifty‐seven studies assessing injections in major joints were identified (see online supplementary Appendix 1) [5‐61]. A majority of the studies (49/57 [86%]) [6,7,9,11‐13,15,17‐25,27‐30,32‐51,53‐61] evaluated injections in a single joint, whereas 14% (8/57) [5,8,10,16,26,31,52,55] assessed injections in more than one joint.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fifty‐seven studies assessing injections in major joints were identified (see online supplementary Appendix 1) [5‐61]. A majority of the studies (49/57 [86%]) [6,7,9,11‐13,15,17‐25,27‐30,32‐51,53‐61] evaluated injections in a single joint, whereas 14% (8/57) [5,8,10,16,26,31,52,55] assessed injections in more than one joint.…”
Section: Resultsmentioning
confidence: 99%
“…Fifty‐seven studies assessing injections in major joints were identified (see online supplementary Appendix 1) [5‐61]. A majority of the studies (49/57 [86%]) [6,7,9,11‐13,15,17‐25,27‐30,32‐51,53‐61] evaluated injections in a single joint, whereas 14% (8/57) [5,8,10,16,26,31,52,55] assessed injections in more than one joint. Thirty‐five percent (20/57) of the studies evaluated knee injections [8‐10,13,15,16,19‐23,26,31,32,36,37,48,52,56,57], 46% (26/57) evaluated glenohumeral (GH) joint injections [5,7,8,10,11,15‐17,24‐26,28,29,31,38‐40,42,43,46,47,49,52,54,60,61], 21% (12/57) evaluated hip injections [8,12,27,30,33,35,41,44,45,50,52,59,62], and 4% (2/57) evaluated sacroiliac (SI) joint injections [18,34].…”
Section: Resultsmentioning
confidence: 99%
“…The level of evidence for a majority of the studies evaluating major joint USGI accuracy (15/23 (65%))5 8 9 15 16 18 20 21 23 27 30 32 34 36–39 41 42 44–46 49 or LMGI accuracy (28/28 (100%))5 7 9–13 17 19 21–26 28 31 32 36–38 40 43 47 48 50 60 61 were level 1 or 2. The mean accuracy of GH, hip and knee joint USGIs in studies with level 1 or 2 evidence ranged from 91% to 100%,5 8 9 15 18 21 23 32 36–39 42 46 49 whereas the mean accuracy of LMGIs were between 64% and 81% 5 7 9–13 17 19 21–26 28 31 32 36–38 40 43 47 48 50 60 61.…”
Section: Resultsmentioning
confidence: 99%
“…Obesity may also affect the accuracy of IA injections (Hurdle, Wisniewski, & Pingree, 2012;Jackson et al, 2002) particularly if performed without any imaging techniques. For example, in a recent case report, a morbidly obese woman had previously undergone four nonguided IA knee injections that did not provide pain relief (Hurdle et al, 2012).…”
Section: Ha Injection Techniquementioning
confidence: 99%
“…Obesity may also affect the accuracy of IA injections (Hurdle, Wisniewski, & Pingree, 2012;Jackson et al, 2002) particularly if performed without any imaging techniques. For example, in a recent case report, a morbidly obese woman had previously undergone four nonguided IA knee injections that did not provide pain relief (Hurdle et al, 2012). Under the guidance of ultrasound technology, the patient was successfully injected with a mixture of corticosteroid and local anesthetic resulting in immediate and complete pain relief (Hurdle et al, 2012).…”
Section: Ha Injection Techniquementioning
confidence: 99%